Burkholderia ambifaria XN08: A plant growth-promoting endophytic bacterium with biocontrol potential against sharp eyespot in wheat - An, Chao; Ma, Saijian; Liu, Chen; Ding, Hao; Xue, Wenjiao (Frontiers in Microbiology, 2022)
Plant growth promoting bacteria (PGPB) have been considered as promising biological agents to increase crop yields for years. However, the successful application of PGPB for biocontrol of sharp eyespot in wheat has been limited, partly by the lack of knowledge of the ecological/environmental factors affecting the colonization, prevalence and activity of beneficial bacteria on the crop. In this study, an endophytic bacterium XN08 with antagonistic activity against Rhizoctonia cerealis (wheat sharp eyespot pathogenic fungus), isolated from healthy wheat plants, was identified as Burkholderia ambifaria according to sequence analysis of 16S rRNA. The antibiotic synthesis gene amplification and ultra-performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-MS) analyses were used to characterize the secondary metabolites. The results showed that the known powerful antifungal compound named pyrrolnitrin was produced by the strain XN08. In addition, B. ambifaria XN08 also showed the capacity of phosphate solubilization, indole-3-acetic acid (IAA), protease and siderophore production in vitro. In the pot experiments, a derivate strain carrying GFP (green fluorescent protein) gene was used to observe its colonization in wheat plants. The results showed that GFP-tagged B. ambifaria could colonize in wheat tissues effectively. This significant colonization was accompanied by an enhancement of wheat plants growth and an induction of immune resistance for wheat seedlings, which was revealed by the higher activities of polyphenol oxidase (PPO), peroxidase (POD), and phenylalanine ammonia-lyase (PAL). As far as we know, this is the first report describing the colonization traits of B. ambifaria in wheat plants. In addition, our results indicated that B. ambifaria XN08 might serve as a new effective biocontrol agent against wheat sharp eyespot disease caused by R. cerealis.